A constitutional predisposition to breast cancer-related lymphoedema and effect of axillary lymph node surgery on forearm muscle lymph flow. Issue 1 (February 2015) - Bains, S.K.; Stanton, A.W.B.; Cintolesi, V.; Ballinger, J.; Allen, S.; Zammit, C.; Levick, J.R.; Mortimer, P.S.; Peters, A.M.; Purushotham, A.D.
Abstract: Aim: The aims of this prospective study were (a) to examine the relationship between pre-operative muscle lymph flow and the predisposition to BCRL in women treated by axillary nodal surgery for breast cancer; and (b) to test the 'stopcock' hypothesis that axillary lymph node surgery impairs forearm lymph flow in the short term. Methods: 99m Tc-nanocoll was injected intramuscularly into both forearms of women undergoing surgery for breast cancer. Lymphatic clearance rate constant, k, representing lymph flow per unit interstitial fluid volume, was measured as the fractional disappearance rate of radioactivity from the depot site by gamma camera imaging. Axillary lymph node activity was calculated as percentage injected activity. BCRL was assessed by clinical examination and upper limb perometry. Results: Of 38 pre-operative women, 33 attended at 8 ± 6 weeks post-operatively and 31 at 58 ± 9 weeks post-operatively. Seven patients (18%) developed BCRL. Prior to surgery the BCRL-destined patients had a higher mean k (0.0962 ± 0.034%/min) than non-BCRL patients (0.0830 ± 0.019%/min) ( p  = 0.10, unpaired t test). Post-operative k values were not significantly different from pre-operative, in either the ipsilateral (operated) or contralateral limb. Also, post-operative k values did not differ significantly between both upper limbs. Furthermore, there was no significant difference between pre- and post-operative axillary activity. Conclusion: Patients who develop BCRL have high lymph flow pre-surgery, which may predispose them to lymphatic overload and failure. Axillary lymph node surgery has no early, measurable effect on forearm muscle lymph flow despite surgical disruption of routes of lymph drainage.